Social media as economic capital: A qualitative study on the digital strategies of fishing communities in Kupang City - Bramason Goma; Lenny Sofia Bire Manoe; Christine Erika Meka; Susana Cecilia Lestyani Pellu (Digital Theory, Culture & Society, 2025)
The advancement of digital technology has opened new opportunities for traditional fishing communities to improve household livelihoods through social media. This study, conducted in Kampung Nelayan Oesapa, Kupang City, examines how social media is utilized as an economic strategy by local fishers. Using a qualitative descriptive approach, the research involved five purposively selected participants who actively use Facebook and WhatsApp to market their catch. Data was collected through observation, in-depth interviews, and documentation, and analyzed using descriptive and triangulation techniques. The findings show that social media plays an important role in disseminating weather information for fishing planning, providing market price information that strengthens fishers’ bargaining positions, and expanding distribution networks beyond the local community. However, several challenges remain, including limited digital literacy, unstable internet connectivity, and social resistance among community members unfamiliar with technology. The study concludes that social media functions not only as a communication medium but also as a form of economic capital that transforms traditional fish marketing practices. This research contributes to the understanding of social media use in maritime communities and offers practical insights for promoting digital- based economic empowerment in coastal areas.